2008
DOI: 10.1093/humrep/den344
|View full text |Cite
|
Sign up to set email alerts
|

A potential tolerogenic immune mechanism in a trophoblast cell line through the activation of chemokine-induced T cell death and regulatory T cell modulation

Abstract: RANTES promotes an adequate pro-implantatory microenvironment that influences trophoblast cell survival and modulates the balance of maternal Treg/T effector lymphocytes in favor of maternal tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 24 publications
1
58
0
2
Order By: Relevance
“…Unlike villous trophoblast, which seems to only marginally express CCL5, trophoblast cell lines Swan 71 and HTR-8/SVneo clearly produce CCL5 (ref. 23) and, moreover, show increased CCL5 secretion in response to lipopolysaccharide (LPS) and TNF-α. 24,25 Although increased CCL5 release in response to inflammatory stimuli is in line with the present study, it remains an open question whether basal CCL5 production found in trophoblast cell lines is the result of their immortalization or reflects their rather extravillous phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike villous trophoblast, which seems to only marginally express CCL5, trophoblast cell lines Swan 71 and HTR-8/SVneo clearly produce CCL5 (ref. 23) and, moreover, show increased CCL5 secretion in response to lipopolysaccharide (LPS) and TNF-α. 24,25 Although increased CCL5 release in response to inflammatory stimuli is in line with the present study, it remains an open question whether basal CCL5 production found in trophoblast cell lines is the result of their immortalization or reflects their rather extravillous phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…There, both factors may interfere with either circulating maternal blood cells or the trophoblast. Although CCL5 may increase Tregs and induce apoptosis of maternal alloactivated T cells in favor of maternal tolerance, 23 GM-CSF may act on the villous trophoblast in an autocrine manner. 26 Indeed, GM-CSF receptor subunit GM-Rα is present on first trimester cytotrophoblast, extravillous trophoblasts, and at lower levels on the syncytiotrophoblast.…”
Section: Discussionmentioning
confidence: 99%
“…28 CCL5 promotes a Th1 profile and an adequate proimplantatory microenvironment, influencing trophoblast cell survival and balance of maternal T regulatory/T effector lymphocytes in favor of maternal tolerance. 29 CXCL12/CXCR4 crosslinking stimulates antiapoptotic pathways in cultured trophoblasts, suggesting that they are important in trophoblast survival. 30 CX3CR1 is present on invading human trophoblasts and promotes their migration by action of its ligand CX3CL1, which is expressed by endometrial vasculature, epithelial and decidual cells during early pregnancy.…”
Section: Immune Response In Acquired Toxoplasmosismentioning
confidence: 99%
“…This molecule can additionally induce apoptosis of potentially harmful maternal CD3 + cells and increases the frequency of Treg. 64 Another molecule in the focus of the review by Perez Leiros is vasoactive intestinal peptide (VIP), whose anti-inflammatory and tolerogenic effects were already known. 65 It is now known that VIP levels rise at the fetal-maternal interface at early gestation peaking at placentation begin.…”
Section: Modulators Of the Immune Responses During Pregnancymentioning
confidence: 99%
“…67 Current data position VIP as an important immunomodulatory molecule as it can increase the frequency of Treg and LIF at implantation sites in mice 68 and supports a tolerogenic macrophage phenotype. 64 It seems that both hormones and polypeptides are involved in the recruitment of immune cells into the fetal-maternal interface and in the generation of a tolerogenic immune response toward the fetus.…”
Section: Modulators Of the Immune Responses During Pregnancymentioning
confidence: 99%